Direct Instruction Aproach (DIA) Untuk Meningkatkan Kinerja Guru Dalam Pembelajaran: Di SD Negeri 1 Sumbergirang - Suyatno, Suyatno (Universitas Cokroaminoto Yogyakarta, 2022)
This research was carried out from July to December 2019 at SD Negeri 1 Sumbergirang with the source of the data being the review of informants and the results of observations. Data validation was carried out through data triangulation and review of informants with data analysis carried out on the results of observation data, data analysis and analysis of interview results. This study consisted of two cycles, each of which consisted of planning, implementing, observing and reflecting. The results showed that the teacher's ability to manage learning could be improved by applying a direct instruction approach. Principals in carrying out their duties have a direct interest in teachers, especially in fostering and developing teacher skills and knowledge related to the development of learning management. The application of the DIA approach is proven to be able to improve teacher performance, especially in managing learning, namely the level of professional ability of teachers in the pre-cycle from 63.95% to 82.99% at the end of the second cycle, meaning an increase of around 19.04%.